Nrf2 Mediates Metabolic Reprogramming in Non-Small Cell Lung Cancer - Zhao, Jiangang; Lin, Xu; Meng, Di; Zeng, Liping; Zhuang, Runzhou; Huang, Sha; Lv, Wang; Hu, Jian (Frontiers in Oncology, 2020)
Nuclear factor erythroid-2-related factor-2 (NFE2L2/Nrf2) is a transcription factor that regulates the expression of antioxidant genes. Both Kelch-like ECH-associated protein 1 (Keap1) mutations and Nrf2 mutations contribute to the activation of Nrf2 in non-small cell lung cancer (NSCLC). Nrf2 activity is associated with poor prognosis in NSCLC. Metabolic reprogramming represents a cancer hallmark. Increasing studies reveal that Nrf2 activation promote metabolic reprogramming in cancer. In this review, we discuss the underlying mechanisms of Nrf2-mediated metabolic reprogramming and elucidate its role in NSCLC. Inhibition of Nrf2 can alter metabolic processes, thus suppress tumor growth, prevent metastasis, and increase sensitivity to chemotherapy in NSCLC. In conclusion, Nrf2 may serve as a therapeutic target for the treatment of NSCLC.